Novel Coronavirus (COVID-19): Violence, Reproductive Rights and Related Health Risks for Women, Opportunities for Practice Innovation - Viveiros, Nelia (Journal of family violence, 2022)
While the novel coronavirus (COVID-19) has broad health implications across the globe, being overlooked in response and policy debates is the impact on women’s reproductive rights and violence risk. This is especially salient for minoritized women. In this commentary, we describe the potential negative impact of mandates such as shelter-in-place for domestic violence victims, and how public reproductive health policy is being shaped to disadvantage women, especially minoritized women. We argue that now is the time for violence prevention leaders to advocate for bold action. This includes prioritizing the needs of women (especially minoritized women) in medical, social and legal settings using innovative intervention and service engagement (e.g., e-filing for protection orders, virtual advocacy services), urging policy makers to pass legislation to support women, and shining an accountability spotlight on leadership.